Peningkatan Softskill Penulisan Tugas Akhir pada Mahasiswa Program Studi Manajemen Bencana Fakultas Ekonomi dan Bisnis Universitas Budi Luhur Melalui Pelatihan Penggunaan Mendeley - Endah Sri Wahyuni; Yuphi Handoko Suparmoko; Hayatul Khairul Rahmat (Yayasan REDI Tiga Monas, 2024)
Writing citations is very crucial in a scientific work because writing techniques and citations describe the quality of the scientific work we create. Therefore, it is important to introduce the citation application to students in the Disaster Management Study Program, Faculty of Economics and Business, Budi Luhur University. The aim of this community service activity is to introduce the use of the Mendeley application to students and provide motivation to write quality scientific papers with correct citations. Increasing students' ability to cite scientific papers will increase students' ability to complete their final assignments later.